2010
DOI: 10.1038/laban0410-107
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of footwear disinfection and shoe cover use in an animal research facility

Abstract: Although the amounts of money and time associated with using shoe covers or other means to prevent floor contamination in animal research facilities can be substantial, the most effective policies and practices remain unknown. In this study, the authors subjected six occupied rodent holding rooms in their animal research facility to three conditions: use of disinfectant mats; use of shoe covers; and no disinfectant mats or shoe covers. The authors took bacterial culture samples from the rooms under each condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 13 publications
0
9
0
1
Order By: Relevance
“…Two studies performed by Allen et al . (, ) as well as Copp et al . () demonstrated that shoe covers may be effective in reducing bacterial contamination.…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…Two studies performed by Allen et al . (, ) as well as Copp et al . () demonstrated that shoe covers may be effective in reducing bacterial contamination.…”
Section: Resultsmentioning
confidence: 72%
“…Allen et al . () reported that Virkon (a chemical mixture of oxone, sodium dodecylbenzenesulfonate, sulfamic acid and inorganic buffer) was able to significantly decrease the mean bacterial count ( P = 0·0015).…”
Section: Resultsmentioning
confidence: 99%
“…This test has strong linear predictability and has been used in previous studies involving the assessment of organic contamination of cage accessories. 2,3,6,16,42,53 We took samples from a 4 ×4 cm area on each wire bar insert and filter top lid of each cage and evaluated the swab for organic contamination in the form of ATP (expressed as relative light units (RLU)) by using luciferase test swabs (PocketSwab Plus, Charm Sciences, Lawrence, MA) and using the same methodology described in a similar study. 42 Swabs were taken at day 0 (prior to housing animals in each cage to verify no organic contamination) 7 d, 14 d, 30 d, 60 d, and 180 d (filter top lids only) after an initial cage change.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, this approach can be considered the gold-standard methodology to use for evaluation of sanitization practices. 2,3,6,16,42,53 Currently, we house mice and rats in static cages that are changed at 1-wk intervals, and individually ventilated cages that are changed at 2-wk intervals. Cages are spot-checked on days not scheduled for a full cage change, and a cage is changed if it meets established cage change criteria.…”
mentioning
confidence: 99%
“…Використання засобів індивідуального захисту суттєво обмежує ризик поширення хвороб [9]. Для мінімізації забруднення взуття працівників запропоновано застосовувати одноразові бахіли, обладнувати дезкилимки з використанням дезінфектантів [10]. Проте, надягання бахіл може призвести до забруднення рук персоналу при контакті з підошвою взуття [11].…”
unclassified